The Polychaeta of Tristan da Cunha. - Day, J.H. (Results of the Norwegian Scientific Expedition to Tristan da Cunha 1937-1938, 1954)
[None. Work starts as:] This paper represents the analysis of two Polychaet collections. The larger was made by the Norwegian Scientific Expedition to Tristan da Cunha, Nightingale and Inaccessible Islands under the leadership of Erling Christophersen during the period December 1937 to March 1938. Collections were made by hand between the tide marks and by dredging at various depths down to 60 metres. The second was made by Dr. G. J. Broekhuysen and Mr. W. Macnae of the University of Cape Town. They acted as biologists to an expedition organized by the Lamberts Bay Canning Co. in February 1948 to test the possibility of establishing a rock-lobster fishery on Tristan da Cunha.
World Polychaeta Database (WPolyDb). Not known to be online digitised, except here